2018
DOI: 10.3389/fpsyt.2018.00394
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition and Activation Systems, and Emotional Regulation in Individuals With Chronic Musculoskeletal Pain

Abstract: Gray's Reinforcement Sensitivity Theory postulates two distinct neurophysiological systems that underlie thoughts, emotions, and behavior: the Behavioral Inhibition System (BIS) and the Behavioral Approach System (BAS). Preliminary research suggests that both systems may play relevant roles in the adjustment of individuals with chronic pain. However, there is a lack of research on the extent to which emotional regulation (i.e., cognitive reappraisal and expressive suppression) mediates the associations between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 64 publications
(91 reference statements)
4
21
0
Order By: Relevance
“…42 One previous study suggests that the association between BIS and negative affect is mediated by expressive suppression. 21 These findings are in line with our results. One possible explanation for our surprising finding is that the behavioral inhibition induced by BIS may suppress elderly people's ability to face their thoughts, thus making adaptive strategies more difficult.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…42 One previous study suggests that the association between BIS and negative affect is mediated by expressive suppression. 21 These findings are in line with our results. One possible explanation for our surprising finding is that the behavioral inhibition induced by BIS may suppress elderly people's ability to face their thoughts, thus making adaptive strategies more difficult.…”
Section: Discussionsupporting
confidence: 93%
“…However, our results are inconsistent with those of studies on adults with chronic pain, which find no association between BAS and emotional regulation. 21 One possible explanation for this inconsistency is that individuals in pain may find it difficult to perform adaptive cognitive emotion regulation strategies, and thus may show weaker relationships between BAS and adaptive strategies. 39 Further, socioemotional selectivity theory states that older people can more effectively adjust their emotions, 40 which may suggest that those with higher BAS sensitivity are more apt to implement adaptive strategies effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the previous idea, research in the past decades has shown psychological factors clearly contribute to a better understanding of the experience of chronic pain (Edwards et al, 2016; Linton et al, 2018; Serrano-Ibáñez et al, 2018). For instance, catastrophizing, a maladaptive form of thinking characterized by a tendency to exaggerate, worry, and anticipate the worst possible consequences of an event (Leung, 2012; Ramírez-Maestre et al, 2017), has been consistently associated with poorer health status of pain patients across numerous investigations (Vancleef and Peters, 2006; Burns et al, 2015; Fallon et al, 2015; Ramírez-Maestre et al, 2017) and has become a fundamental outcome in pain research (Williams et al, 2013).…”
Section: Introductionsupporting
confidence: 71%
“…High BIS is associated with enhanced attention, arousal and vigilance, high BAS with impulsivity, bipolar and attention deficit/ hyperactivity (De Pascalis et al, 2010 ). In particular, BIS/BAS modulates pain in patients with headache (Jensen et al, 2015 ) and muskuloskeletal pain (Serrano-Ibáñez et al, 2018 ).…”
Section: Interaction Of Hypnotisability With the Behavioral Inhibitiomentioning
confidence: 99%